2017
DOI: 10.1080/09540121.2017.1390540
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Mother-to-Child Transmission of HIV in Yaounde: Barrier to Care

Abstract: Most HIV-infected children in Sub-Saharan Africa are born where programs for the prevention of mother-to-child transmission of HIV (PMTCT) exist but are not universally operational. The expansion of PMTCT programs in Cameroon was among the largest in francophone Africa, but despite highly variable estimates of PMTCT uptake (ranging from 20% to 66%), it is clear that not enough HIV-infected pregnant Cameroonian women benefit from treatment to prevent HIV transmission to their children. The reasons why HIV-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In countries of Sub-Saharan Africa (SSA) like Uganda, the risk of HIV infection during adolescence is high [2]. Moreover, vertical transmissions of HIV continue to occur in these countries due to low access to perinatal health care services [3]. As a result, the prevalence of HIV in Ugandan youth is on an upward trend.…”
Section: Introductionmentioning
confidence: 99%
“…In countries of Sub-Saharan Africa (SSA) like Uganda, the risk of HIV infection during adolescence is high [2]. Moreover, vertical transmissions of HIV continue to occur in these countries due to low access to perinatal health care services [3]. As a result, the prevalence of HIV in Ugandan youth is on an upward trend.…”
Section: Introductionmentioning
confidence: 99%
“…More than a decade since the implementation of the Prevention of Mother-to-Child Transmission (PMTCT) programme of HIV, more than 90% of pregnant women are said to know their HIV status, the percentage of women living with HIV accessing antiretroviral treatment is estimated to have increased from 65% in 2010 to 87% in 2018 and there has been an 84% reduction in HIV infected newborns [4][5][6][7][8][9]. However, despite these strides and advances in HIV care including universal test and treat [10,11], there is still persistence of incident maternal and newborn HIV infections [4][5][6][7][8][9]. Vertical transmission of HIV from mother to child can take place during pregnancy, delivery and lactation [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary a cross-sectional study in Zambiaand another in South Africa found no association between maternal decision making autonomy and adherence to infant prophylaxis [20,21]. In addition, a Cameroonian qualitative therapeutic itineraries study of barriers or impediments to ART adherence were found to include financial constraints, limited social support and limited information on HIV/AIDS and treatment [22].…”
Section: Introductionmentioning
confidence: 91%